Imiona słowiańskie z członami lubo-, -lub, miło-, -mił w toponimii Polski - Górny, Halszka (Słowo. Studia językoznawcze, 2019)
The article is devoted to toponyms motivated by Slavic compound names with adjective elements: lubo-, -lub, miło-, -mił. This topic is part of the research project called “Names as the Basis of Polish Geographical Names”, carried out at the Institute of the Polish Language at the Polish Academy of Sciences in Cracow. In a two-line analysis (on the antroponymic and toponymic level), enriched with cartographic illustrations, attention was focused on pointing out the chronology of personal names, productivity of the Slavic names in the process of nominating toponyms, and on highlighting the chronology, frequency, geography of oikonyms and their structural types. In over 60 place names created up to the end of the 16th century, and located mainly in Greater Poland, Silesia and Mazovia, 27 names with the above-mentioned elements were preserved. Among them are forms reconstructed from toponyms, such as: *Lubogost, *Lubomysł, *Lubowid, *Lubowit, *Nielub, *Miłobąd, *Miłodrog, *Miłorad, *Niemił. The younger layer of place names dated to the eighteenth and nineteenth centuries or introduced officially after 1945 occur mainly in the north and west of Poland.